Keterlibatan Perempuan dalam Aksi Terorisme di Indonesia - Sityi Maesarotul Qori’ah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
The bomb blast in Surabaya which was an act of terrorism carried out by one family showed that women were actively involved in acts of terrorism. In the early days of the emergence of terrorism, women only acted as intermediaries, managing data through the internet network, fund collectors and driving